1954
DOI: 10.1080/17470215408416657
|View full text |Cite
|
Sign up to set email alerts
|

A Further Study of the Pendulum Phenomenon

Abstract: 4 first series of experiments had demonstrated certain conditions eliciting or inhibiting a "pendulum" phenomenon in the visual perception of apparent movement. The present study consists of five further variations designed to show more clearly conditions of occurrence and non-occurrence of this type of movement.Altering the axis of display to vertical significantly reduces the frequency of pendular-movement perception; Altering the position of metronome from behind to the side of the visual display, gives res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1957
1957
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…For example, the results of experiments in which the participants had to discriminate the location of target stimuli in one sensory modality while trying to ignore the distractor stimuli presented (at the same time) in a different modality, as in many studies that have been conducted using the cross‐modal congruency task, typically obey the spatial rule: distractors situated close to the target tend to exert a significantly larger effect on the speed and accuracy of participants’ performance than targets situated further away, regardless of the specific posture adopted by the participant (e.g., whether a participant's hands are placed in a crossed or uncrossed posture when investigating visuotactile interactions). A similar spatial modulation of participants’ behavioral performance has also been documented in those studies in which the participants have had to judge the direction of apparent motion of the stimuli presented in one modality (another task that is, in some sense, spatial) while simultaneously trying to ignore the distractor apparent motion presented in another modality …”
Section: The Spatial Rule: Just When Does Spatial Coincidence Facilitsupporting
confidence: 71%
See 1 more Smart Citation
“…For example, the results of experiments in which the participants had to discriminate the location of target stimuli in one sensory modality while trying to ignore the distractor stimuli presented (at the same time) in a different modality, as in many studies that have been conducted using the cross‐modal congruency task, typically obey the spatial rule: distractors situated close to the target tend to exert a significantly larger effect on the speed and accuracy of participants’ performance than targets situated further away, regardless of the specific posture adopted by the participant (e.g., whether a participant's hands are placed in a crossed or uncrossed posture when investigating visuotactile interactions). A similar spatial modulation of participants’ behavioral performance has also been documented in those studies in which the participants have had to judge the direction of apparent motion of the stimuli presented in one modality (another task that is, in some sense, spatial) while simultaneously trying to ignore the distractor apparent motion presented in another modality …”
Section: The Spatial Rule: Just When Does Spatial Coincidence Facilitsupporting
confidence: 71%
“…modality (another task that is, in some sense, spatial) while simultaneously trying to ignore the distractor apparent motion presented in another modality. [74][75][76] Researchers investigating the ventriloquism effect, which can be considered a spatial localization (or sometimes a discrimination) task, have also repeatedly demonstrated that the strongest multisensory spatial interactions occur when stimuli from different modalities are presented close to one another, and that the effect declines as separation of auditory and visual stimuli increases. 25,77,78 Such results, with a task that is unequivocally spatial, also clearly fit the spatial rule.…”
Section: Covert Orientingmentioning
confidence: 99%
“…Zapparoli and Reatto (1969) found that the direction of visual motion determined whether auditory AM was facilitated and interfered with. Finally, Hall et al (1952) and Hall and Earle (1954) showed that the path of visual AM was curved when accompanied by synchronous audio stimuli.…”
Section: Integration Of Bimodal Audiovisual Ammentioning
confidence: 94%
“…Livson (1953) examined the after-effect of prolonged inspection of AM with relation to autokinetic movemenc. Hall and Earle (1954) changed the location of a metronome from the back of to the side of an AM display and produced results almost identical to those where the metronome was inaudible. Shapiro ( 1954) continuously stimulated one eye with an inspection figure located in the path of AM seen through the other eye and found a rise in threshold for optimal move-ment.…”
Section: Experimental Studies Type Of Movenzentmentioning
confidence: 99%